2022
DOI: 10.1088/1361-6498/ac6274
|View full text |Cite
|
Sign up to set email alerts
|

Optimising whole body computed tomography doses for paediatric trauma patients: a Swiss retrospective analysis

Abstract: Objective: We aimed to evaluate the impact of a low-dose whole-body computed tomography (WBCT) protocol on radiation doses in pediatric major trauma patients. Methods: Retrospective cohort study of pediatric trauma patients (<16 years) at a national level 1 pediatric trauma center (PTC) over a 6-year period prior and post introduction of a low-dose WBCT protocol (2014–2019). Demographic data, patient characteristics, CT device, and exposure information including scan range, dose-length product (DLP), and vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…Other studies have reported a low adherence to imaging guidelines [ 36 , 37 ], raised concerns about the use of CT in hemodynamically stable patients [ 38 ], and shown high variability in imaging practice among trauma centers [ 39 , 40 ]. For patients in our cohort, a low-dose WBCT protocol was in place, limiting radiation exposure below the annual background radiation dose [ 41 ]. Thus, imaging should take place at a pediatric trauma center whenever possible [ 37 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported a low adherence to imaging guidelines [ 36 , 37 ], raised concerns about the use of CT in hemodynamically stable patients [ 38 ], and shown high variability in imaging practice among trauma centers [ 39 , 40 ]. For patients in our cohort, a low-dose WBCT protocol was in place, limiting radiation exposure below the annual background radiation dose [ 41 ]. Thus, imaging should take place at a pediatric trauma center whenever possible [ 37 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…They were listed according to Sillence classification into type III (17) and type IV (5). The indications for the surgery were as follow: fracture (12), correction of deformity (20) or treatment of non-union (4). In all cases, allografting was added to compensate areas of fragility and in 28 cases they were used as a means of fixation to provide structural support and to avoid the need for plate fixation.…”
Section: Allografting Is An Effective Biological Methods Of Fixation ...mentioning
confidence: 99%
“…In certain fractures, follow-up radiographs may be necessary to accommodate this low diagnostic accuracy, especially in the context of suspected abuse, thus necessitating additional exposure to a relatively high radiation dose. Whole-body radiography imparts a mean radiation dose of approximately 0.20 mSv, 17 roughly the equivalent of 1 month of typical background radiation in the UK; 18 mean effective doses experienced during wholebody imaging using the other modalities discussed range from 0 mSv for methods that do not employ ionizing radiation (MRI and ultrasound), up to 0.001 mSv for dual X-ray absorptiometry (DXA), 19 2.3 mSv for nuclear medicine imaging 17 and 4.8 mSv for a low-dose CT. 20 CT provides cross-sectional imaging generated from multiple X-ray measurements at different angles, facilitating multiplanar examinations and threedimensional (3D) reconstructions. The technique is relatively rapid -a whole-body CT scan can be performed in the duration of a single breath-hold (compared with 30 minutes or more for a conventional radiographic skeletal survey), but whole-body CT scans are not commonly performed and, therefore, CT is not used to provide an overview of proportions.…”
Section: Fracture Determination In the Abnormal Skeletonmentioning
confidence: 99%
“…Nevertheless, some centres have implemented low-dose WBCT protocols, featuring a mean radiation dosage of 4.8 mSv, in contrast to normal dose protocols with an average radiation dosage of about 20.6 mSv. Therefore, low-dose WBCT significantly reduces the radiation dose by approximately 77% (29).…”
Section: Musculoskeletal Systemmentioning
confidence: 99%